ENHANCING READING LITERACY AND TEACHER ENGAGEMENT THROUGH READS ROADMAPS AND INTERACTIVE E-BOOK - Syahmina; Fitrawati (University of Kuningan, 2026)
Reading literacy remains a major challenge in Indonesian junior high schools, where many students still struggle to understand texts beyond the literal level, while teachers often face difficulties in sustaining effective reading instruction. These problems are closely related to limited teacher engagement and the lack of integration between structured literacy strategies and digital learning resources. Although previous studies have discussed structured reading models or digital tools separately, empirical evidence that combines both while addressing teacher reading engagement remains limited. This study aimed to investigate the implementation of READS Roadmaps integrated with interactive e-books and to examine their contribution to improving students’ reading literacy and teachers’ reading engagement. Using a Classroom Action Research design, the study was conducted in three cycles with eighth-grade students at a public junior high school in Padang. Data were collected through classroom observations, reading literacy tests, questionnaires, interviews. The findings showed a sustained improvement in students’ reading literacy across the cycles, particularly in inferential and evaluative reading. In addition, teachers demonstrated higher motivation, confidence, and more active involvement in planning and delivering reading instruction. Overall, the results indicate that integrating READS Roadmaps with interactive e-books offers a practical and effective approach to enhancing reading literacy and strengthening teacher engagement in junior high school contexts.